PERAN ORGANISASI IPNU DAN IPPNU DALAM PEMBINAAN KEPRIBADIAN REMAJA DI KECAMATAN JOGONALAN, KLATEN - Samsudin Asrofi; Imam Safi’i; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses the role of the IPNU IPPNU organization in fostering the personality of adolescents in Jogonalan District, Klaten. This research was motivated by teenagers who were wrong in the association which resulted in bad relationships, so that IPNU IPPNU Jogonalan, Klaten gave its role in shaping the personality of teenagers in the Jogonalan District, Klaten. The methodology used in this research is qualitative, using a case study type. With training and activities or work programs, IPNU IPPNU members will be even better, among which activities are administrative training, organizational discussions, tahlil, prayers and pilgrimages. This method is one of the PAC IPNU IPPNU Jogonalan programs in fortifying its members or cadres to become even better.